Rachunek zysków i strat jako źródło informacji o działalności jednostek budżetowych - Rudnicka, Bożena (Profit and Loss Account as a Source of Information about Activity of Budgetary Units, 2007)
Budgetary units have been obliged to making profit and loss account. Its composition, position names and outcomes of particular segments are based on formula of profit and loss account with the classification of expenses by type of income units. Thereby, not conducting income activity and not instantiating incomes from sale, those units have in this account loss from sale and from economic activity. Ipso facto there is justified doubt about validity of that solution and about understanding of communicating account recipents about information.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 434-442